Pengaruh Kompres Bawang Merah Allium Cepa Var Aggregatum Terhadap Nyeri Sendi Penderita Gout Arthritis di Wilayah Kerja Puskesmas Tuminting Kota Manado - Adi Saputro; Rahmat Hidayat Djalil; Zainar Kasim (STIKES Columbia Asia Medan, 2023)
Gout Arthritis is an inflammatory joint disease caused by the accumulation of monosodium urate crystals in the body. Onion compress is a current form the treatment of gout arthritis with no side effects. The aim of this research is a to determine the effectivennes of shallot (Allium Cepa Var Aggregatum) compress on joint pain Gout Arhtritis patients at the Working Area, Public Health Center Tuminting Manado. The research conducted by using a pre-experimental (pre and post test design). The samples were 13 subjekts which taken using total sampling technique. Research instruments used observation sheet and SOP for measurement with the NRS (Numeric Rating Scale). Analyzed data by using a Wilcoxon test with the significance level α = 0,01. The results of this research obtained a value p=0.002 (α≤0.05), which means that Ha is accepted and Ho is rejected, so that can be concluded there were an effectivennes of shallot (Allium Cepa Var Aggregatum) compress on joint pain Gout Arhtritis patients at the Working Area, Public Health Center Tuminting Manado. The conclusion of this research is that there is an effectivennes of shallot (Allium Cepa Var Aggregatum) compress on joint pain Gout Arhtritis patients at the Working Area, Public Health Center Tuminting Manado. Advice to subjekts who often experience gout arthritis pain is to treat it themselves by using shallot compresses.